Two centuries of Irish agriculture - a statistical retrospect, 1672-1905 - Chart, D.A. (Statistical and Social Inquiry Society of Ireland, 1912)
In economic, as in political problems, a knowledge of the past is essential to the proper understanding of the present. At this time, therefore, when so many Irishmen are hoping and striving for a general industrial revival, it may not be inappropriate to trace the fortunes of our oldest, most important, and perhaps, most successful industry?that connected with the land.
Read, March 20th, 1908.
Keywords: Agriculture, Ireland; Farming methods, Ireland; 314.15